2019
DOI: 10.1088/1361-6404/ab25fc
|View full text |Cite
|
Sign up to set email alerts
|

University students’ ideas about the role of the aperture and laser beam dimensions in formation of diffraction patterns

Abstract: Successful application of the Huygens–Fresnel principle often requires reasoning about the interplay of aperture and light beam dimensions for purposes of identifying the unobstructed part of the light beam which is the source of secondary waves. Therefore we decided to identify university students’ ideas about the role of this interplay in the formation of diffraction patterns. We conducted a survey research with 191 first-year students from the Faculty of Chemical Engineering and Technology at the University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…Students believed that the interference fringes would elongate in the vertical direction which reflects the idea that changes of the height of the slit lead to similar effects as changes of the width of the slit, although for the horizontal dimension of the slit diffraction effects are prominent which cannot be said for the vertical dimension. This finding is in line with the results of the study by Mešić, Vidak, Hasović, and D -ekić, who showed that students exhibit many difficulties in understanding the role of the vertical dimension of the slit [7].…”
Section: B Posttestsupporting
confidence: 91%
See 3 more Smart Citations
“…Students believed that the interference fringes would elongate in the vertical direction which reflects the idea that changes of the height of the slit lead to similar effects as changes of the width of the slit, although for the horizontal dimension of the slit diffraction effects are prominent which cannot be said for the vertical dimension. This finding is in line with the results of the study by Mešić, Vidak, Hasović, and D -ekić, who showed that students exhibit many difficulties in understanding the role of the vertical dimension of the slit [7].…”
Section: B Posttestsupporting
confidence: 91%
“…Consequently, they often fail to correctly predict what would happen if we would rotate the slits by 90 • . This is probably related to a lack of basic understanding of the Huygens-Fresnel principle [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concretely, students find it very difficult to develop a functional model of the wave optics phenomena (Mešić et al, 2016). Thus, many students believe that the transmission of light through a single slit depends on the amplitude of the sinusoidal wave of light (Ambrose et al, 1999) or that a wider light beam contributes to a wider central maximum diffraction pattern (Mešić et al, 2019b). In addition, they think that diffraction happens as a result of a superposition of the two secondary waves that originate at the two edges of the slit (Ambrose et al, 1999).…”
Section: Students' Ideas About Wave Opticsmentioning
confidence: 99%